Applying cognitive linguistics : figurative language in use, constructions and typology / edited by Ana María Piquer-Píriz, Rafael Alejo-González, University of Extremadura. - Piquer-Píriz, Ana María; Alejo-González, Rafael (Benjamins current topics ;, 2018)
In recent years, Cognitive Linguistics (CL) has established itself not only as a solid theoretical approach but also as an important source from which different applications to other fields have emerged. In this volume we identify some of the current, most relevant topics in applied CL-oriented studies - analyses of figurative language (both metaphor and metonymy) in use, constructions and typology -, and present high-quality research papers that illustrate best practices in the research foci identified and their application to different fields including intercultural communication, the psychology of emotions, second and first language acquisition, discourse analysis and translation studies. It is also shown how different methodologies - the use of linguistic corpora, psycholinguistic experiments or discourse analytic procedures - can shed some light on the basic premises of CL as well as providing insights into how CL can be applied in real world contexts. Finally, all the studies included in the volume are based on empirical data and there are some analyses of languages other than English (Japanese, Russian, Spanish, Danish, German and Polish), thus, overcoming the contentions that CL-theoretically-based research is often based on linguistic intuition and focused only on the English language.0We hope that the present volume will not only contribute to a better understanding of how CL can be applied but that it will also help to encourage, even further, more robust empirical research in this field.0Originally published as a special issue of 'Review of Cognitive Linguistics' 14:1 (2016).- Resumé vydavatel